Україна як соціальна держава: концептуальні положення та конституційно-правові реалії - Крусян, Анжелика Романовна; Крусян, Анжеліка Романівна; Krusyan, Аnjelika R. (My University, 2012)
On the basis of certain doctrines and while analyzing the national Constitutional legal practice, it is possible to come to the conclusion that in a social state the top priority of state policy is the well fare of its citizens. It means that the state creates all necessary conditions to ensure economic, social and cultural rights for the citizens. The state also guarantees social protection and security, based on the social and economic potential of the state and promoting the principle of justice, rationality and harmonic balance of hu- man and society’s interest.
Крусян А. Р. Україна як соціальна держава: концептуальні положення та конституційно-правові реалії / А. Р. Крусян // Актуальні проблеми політики: зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2012. – Вип. 44. – С. 35-47.
Keywords: соціальна держава; конституційно-правова практика; соціальна спрямованість; громадянське суспільство; соціальний захист; соціальна безпека; социальное государство; конституционно-правовая практика; социальная направленность; гражданское общество; социальная защита; социальная безопасность; welfare state; constitutional and legal practice; social orientation; civil society; social Protection; social Security